2013
DOI: 10.1007/s10620-013-2732-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Beclin1 and Impairment of Autophagy in a Small Population of Colorectal Cancer

Abstract: BackgroundAutophagy is a highly conserved mechanism for degradation and recycling of long-lived proteins and damaged organelle to maintain cell homeostasis. Deregulation of autophagy has been associated with tumorigenesis. Beclin 1 is an essential autophagy protein and its upregulation has been observed in most colorectal cancer tissues. However, there is a small population of colorectal cancers with downregulation of Beclin 1.AimThe purpose of this study was to investigate the role autophagy plays in colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…It was previously reported that overexpression of Beclin-1 in vitro inhibited CRC cells growth and enhanced the rapamycin-induced antitumor effects (136). Patients with high levels of Beclin-1 presented good prognosis and longer survival (131, 135), and ATG10 downregulation was associated with cell migration and invasion of CRC cells (137).…”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that overexpression of Beclin-1 in vitro inhibited CRC cells growth and enhanced the rapamycin-induced antitumor effects (136). Patients with high levels of Beclin-1 presented good prognosis and longer survival (131, 135), and ATG10 downregulation was associated with cell migration and invasion of CRC cells (137).…”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%
“…Some evidence has shown that autophagy is highly induced in most CRC patients and CRC cells (130135). However, there is also a small population of CRC patients with downregulated autophagy (136). Based on those reports, the expression profile of autophagy is inconsistent in CRC patients.…”
Section: The Roles Of Autophagy In Ibdmentioning
confidence: 99%
“…In CRC tissues, BECN1 can be either up- or downregulated 184 . The activation of autophagy by overexpressing BECN1 may be an effective treatment of CRC with defects in BECN1 186 . In one study, the expression and significance of 3 autophagy-related proteins, namely BECN1, LC3, and MTOR, were investigated in the tumorigenesis and development of CRC.…”
Section: Inhibitors and Activators Of Autophagy And The Upr In Crcmentioning
confidence: 99%
“…Similar studies also demonstrated that over-expression of Beclin-1 inhabited colorectal cancer cell growth (Chen et al, 2013), and the higher level of Beclin-1 was strongly associated with longer survival (Li et al, 2009). So no certainty outcomes were determined up to now.…”
Section: Introductionmentioning
confidence: 96%
“…The autophagic cancer cell response to ionizing radiation and chemotherapy seems to affect the efficacy of chemotherapy and radiotherapy (Zois and (Chen et al, 2013;Zhang et al, 2013). Though oncogenes and tumor suppressor genes are also involved in the regulation of autophagy, the role of autophagy in the metastasis and prognosis of human colorectal cancer are still poorly understood (Maiuri et al, 2009).…”
Section: Introductionmentioning
confidence: 99%